Genocide and Human Rights - Roth, J. author. aut Link
XXI, 352 p.
Keywords: Genocide is evil or nothing could be. It raises a host of questions about humanity, rights, justice, and reality, which are key areas of concern for philosophy. Strangely, however, philosophers have tended to ignore genocide. Even more problematic, philosophy and philosophers bear more responsibility for genocide than they have usually admitted. In Genocide and Human Rights: A Philosophical Guide, an international group of twenty-five contemporary philosophers work to correct those deficiencies by showing how philosophy can and should respond to genocide, particularly in ways that defend human rights.